Manajemen Pendidikan Islam Berbasis Al-Qur’an: Antara Pemikiran Tokoh Dan Riset - Sabrifha, Eli (CV. SINAR HOWUHOWU, 2026)
Qur'an-based Islamic education management is a systematic effort to make Qur'anic values the philosophical and operational foundation in the governance of Islamic educational institutions. This study aims to analyze the integration of Qur'anic values such as rahmah, adl, amanah, shura, and ihsan. Meanwhile, the functions of educational management include planning, organizing, implementation, and evaluation. Through a qualitative approach and in-depth literature study, this study examines the contributions of classical Islamic figures such as Al-Ghazali, Ibn Khaldun, and Ibn Sina, as well as contemporary figures such as Azyumardi Azra and Fazlur Rahman, in formulating an integrative and value-based management paradigm. The results of the study indicate that Qur'anic values are not only normative, but also functional in forming a just, participatory, and spiritually meaningful organizational culture. The application of the principles of wisdom in planning, fairness in organizing, trustworthiness in implementation, and ihsan in evaluation has proven to be able to create a management system that is not only efficient but also shapes perfect human beings people of faith, knowledge, and noble character. Thus, Qur'an-based Islamic education management is not simply an adaptation of modern management models, but rather a fundamental transformation that makes institutional governance part of the educational and worship process.